Economic diversification and sustainable development in Saudi Arabia: Evaluating the vision 2030 initiative - Ahmed, Awadelkarim Elamin Altahir; MAHMOUD, MUTAZ.T. (International Journal of Innovative Research and Scientific Studies, 2025)
The Saudi Economy is heavily reliant on oil exports, making it vulnerable to fluctuations in international oil prices. This prompted the Saudi Government to introduce different initiatives to diversify its economy, including the Saudi 2030 Initiative, which is aimed to diversify the Saudi economy and promote sustainable development. This study aims to assess the effectiveness of the Saudi 2030 Vision Initiative in terms of promoting economic diversification and evaluate its influence on sustainable development in Saudi Arabia. The study has utilised a mixed method approach, triangulating quantitative data from 300 respondents through a cross-sectional survey and qualitative semi-structured interviews from 15 stakeholders from government, private sector, and academia. This study has revealed that institutional support and human capital development challenges significantly mediate the relationship between the current state of economic diversification and sustainable development outcomes of the Saudi Vision 2030. The qualitative findings highlighted challenges in implementation, such as cultural resistance and regulatory compliance issues. This study has provided a comprehensive assessment of the Vision 2030 Initiative and offered insights to comprehend the complex dynamics of economic transformation and sustainable development in the Saudi context. The result shows that the Saudi 2030 Vision initiative has helped to achieve significant progress in diversifying the economy by creating new non-oil sectors, including information technology, tourism, and renewable energy. The study findings have valuable implications for informing policymakers to establish improved strategies to enhance the effectiveness of diversification efforts.